Sustainable Game Design (Susgad) Framework For Game-Based Learning Development (i-Tajweed) To Motivate Students In Learning Tajweed - Nadiah Binti Ramlan
Many studies related to sustainability have been conducted in numerous fields. However, existing studies in sustainability focus more on the product’s environmental impact of the software engineering domain than sustainability elements in the development process. Since game design is a crucial aspect towards the successful implementation of game-based learning (GBL), the conceptual research on sustainability elements in game design is needed. Therefore, three research objectives were formulated as follows: 1) To identify sustainability elements for GBL in learning Tajweed, 2) To develop interactive GBL in Tajweed using the selected sustainability elements, 3) To evaluate the impact of games-based learning on students’ motivation, students’ achievement and, sustainability elements in GBL. The design and development research (DDR) approach has been utilized in this research by dividing into three phases. ADDIE model (Analyze, Design, Develop, Implement and Evaluate) was used in the process of designing and developing the game. The first phase in DDR involved the need analysis in identifying the sustainability elements. Six sustainability elements, named relevant content, interface design, gameplay, usability, reward, and motivation, have been constructed, designed and validated by eight experts through semi-structured interviews. At the same time, the second phase involved the design and development of a prototype named i-Tajweed. The sustainability elements, Cognitive Theory of Multimedia Learning (CTML), model of instructional design (ID), and motivational technique has been integrated into i-Tajweed. The third phase involved evaluating the prototype and verifying the sustainability elements by conducting the Quasi-Experiment. The inferential analysis used was the t-test and Pearson correlation test. The findings of the independent sample t-test analysis showed that there was a significant difference in students’ achievement between the control group and the treatment group, with a significant value obtained being .002 (p <.05). For the results of Pearson correlation analysis, a significant relationship was shown between sustainability aspects with students’ achievement after exposure to GBL in Tajweed learning, with a significant value obtained being .018 (p<.05). Similarly, there was a relationship between the element of motivation and student`s achievement after being exposed to GBL in Tajweed learning, with the significant value reached being .016 (p<.05). In conclusion, the results show that the use of GBL in learning Tajweed can increase student motivation and, in turn, improve student achievement in learning Tajweed.